Role of Renal Ultrasonography in Predicting Vesicoureteral Reflux and Renal Scarring in Children Hospitalized with a First Febrile Urinary Tract Infection - Tung-Wei Hung; Jeng-Dau Tsai; Pei-Fen Liao; Ji-Nan Sheu (Elsevier, 2016)
This study was designed to examine the capability of renal ultrasonography (US) for predicting vesicoureteral reflux (VUR) and renal scarring (RS), and to assess, using initial US, the significant urologic abnormalities that impact on management of children hospitalized with a first febrile urinary tract infection (UTI). Methods: Hospitalized children aged ≤ 2 years with a first febrile UTI were prospectively evaluated using imaging studies, including 99mTc dimercaptosuccinic acid (DMSA) scan, US, and voiding cystourethrography. Results: Of the 310 children analyzed (195 boys and 115 girls), 105 (33.9%) had abnormal US. Acute DMSA scans were abnormal in 194 children (62.6%), including 89 (45.9%) with concomitant abnormal US. There was VUR in 107 children (34.5%), including 79 (25.5%) with Grades III-V VUR. The sensitivity and negative predictive values of US were 52.3% and 75.1%, respectively, for Grades I-V VUR and 68.4% and 87.8%, respectively, for Grades III-V VUR. Eighty-five children (27.4%) had RS, including 55 (64.7%) with abnormal US. Of the 105 children with abnormal US, 33 (31.4%) needed subsequent management (surgical intervention, parental counseling, or follow up of renal function). Nephromegaly on initial US and Grades III-V VUR were risk factors of RS. Conclusion: Abnormal US may carry a higher probability of Grades III-V VUR and RS, and can affect subsequent management in a significant number of children. Nephromegaly on initial US and Grades III-V VUR are strongly associated with an increased risk for RS. Thus, US should be performed on children after a first febrile UTI and children with normal US may not require voiding cystourethrography.